Pull-out resistance study of mechanical joints on sandwich materials: a review. (2nd January 2023) - Daniel,; Triadi, Syahwira Taqwa; Wirawan, Riza; Prajetelistia, Ekavianty; Judawisastra, Hermawan
ABSTRACT: In applications such light train application, sandwich materials require mechanical joints. One major load produced at the mechanical joining is the pull-out load. The scope of this literature review includes pull-out test results, failure mode during the pull-out test, failure load parameters, and an analytical method to determine the maximum pull-out load. The pull-out resistance of the mechanical joint on sandwich material is determined by the failure load and the maximum load. The failure modes on sandwich material include core buckling, shear cracking, tensile rupture and delamination. The failure load of mechanical joints on the sandwich material will increase as insert depth, insert diameter, core thickness and core density increase. Meanwhile, two analytical methods (Aerospace Engineering and Zenkert Methods) are studied, and it is found that the Aerospace Engineering is more accurate. The multiplier for the maximum load value has been found to determine the failure load.